Eksperimen Model Pembelajaran Group Investigation (Gi) Berbasis Assessment For Learning (Afl) Ditinjau Dari Kemampuan Penalaran Matematis Siswa Terhadap Hasil Belajar Matematika Kelas VIII Semester Genap Di SMP Negeri 2 Gatak Tahun Ajaran 2016/2017 - Mahmudah, Inayati, Muhammad Noor Kholid, S.Pd., M.Pd (2017)
On this research has three purpose. (1) Examine the influence-based learning model of Group Investigation with Assessment for Learning, Group Investigation and expository teaching model of the mathematics student learning outcomes.(2) Examine mathematical reasoning ability to influence the outcome of learning mathematics.(3) Examine interaction between learning models with mathematical reasoning abilities of the mathematics learning outcomes. This research is quantitative quasi. The population in this research is all students of VIII SMP N 2 Gatak on academic year 2016/2017. Sample consisted of three classes, experiment class treated Group Investigation with Assessment for Learning and Group Investigation for control class treated exspository .Technique use Cluster Random Sampling. Methods of data collection used documentation and test. Techniques of analyzed used analysis of variance two path different cell. Before the test analysis is start, the sample must be tested prerequisites, the balance test, test normality and homogeneity test. The result of this research with significance 5% result:(1) There is a difference of influence-based learning model of Group Investigation with Assessment for Learning, Group Investigation and expository teaching model of the mathematics student learning outcomes.(2) There are differences in mathematical reasoning ability to influence the outcome of learning mathematics. (3) There is no intraksi between learning models with mathematical reasoning abilities of the mathematics learning outcomes.